2014
DOI: 10.5901/mjss.2014.v5n23p104
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Conceptual Framework Regarding the Factors Affecting Academics in Higher Education’s Job Dissatisfaction

Abstract: This paper presents a conceptual framework regarding the factors affecting academic job dissatisfaction in higher education, derived from an in-depth survey of the related literature. The aim of this study was achieved by identifying the factors that affect university academics' job dissatisfaction. The main result of this study is the development of a framework, derived from the existing literature, of factors affecting university academics' job dissatisfaction. The findings help to articulate issues related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 32 publications
(26 reference statements)
1
3
0
Order By: Relevance
“…That is, leadership style can only lead to the lecturers' research commitment if there is positive attitude among them, such as interest. This supported Abdulsalam and Mawoli (2012), who argued that motivation could be induced by an employer, and Basak (2014) and Job (2013), who concluded that personal interest was more crucial to research than environment factors.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…That is, leadership style can only lead to the lecturers' research commitment if there is positive attitude among them, such as interest. This supported Abdulsalam and Mawoli (2012), who argued that motivation could be induced by an employer, and Basak (2014) and Job (2013), who concluded that personal interest was more crucial to research than environment factors.…”
Section: Discussionsupporting
confidence: 49%
“…Abdulsalam and Mawoli (2012) argued further that motivation could be induced by the employer or could reside within the employee. Basak (2014) concluded that, though environment factors such as lack of research facilities, difficulty in accessing research grant and scarcity of graduate research assistant could hinder research, personal interest was a more crucial factor. Cherian and Jacob (2013) also concluded that self-belief influences motivation, which leads to employee's job performance.…”
Section: Problem Statementmentioning
confidence: 99%
See 2 more Smart Citations